Analysis of the Implementation of an Internet of Things (IoT) Based Environmental Quality Monitoring System Using Multi-Parameter Sensors - Siska Aprelyani (Siber International Journal of Education Technology (SIJET), 2026)
The implementation of an Internet of Things (IoT) based environmental quality monitoring system using multi-parameter sensors has emerged as a solution to overcome the limitations of conventional monitoring methods, which are unable to provide continuous and real-time data. This study aims to analyze the implementation of an IoT-based environmental quality monitoring system using multi-parameter sensors and evaluate the sensors' performance in measuring various environmental quality parameters in real time. A Systematic Literature Review (SLR) method was employed by analyzing national scientific publications published between 2016 and 2026. The findings indicate that the monitoring system is implemented through the integration of multi-parameter sensors, microcontrollers, communication networks, cloud computing, and monitoring dashboards, enabling automatic and real-time environmental monitoring. Furthermore, the sensors demonstrate satisfactory accuracy, responsiveness, and reliability after proper calibration, although their performance is influenced by environmental conditions and periodic maintenance requirements. The novelty of this study lies in providing a comprehensive synthesis of IoT system implementation and multi-parameter sensor performance within a single analytical framework. In conclusion, IoT-based environmental monitoring systems have significant potential to improve environmental management through accurate, continuous, and real-time data acquisition.